Education and Innovation of Mangrove-Based Products for the Health of Coastal Communities in Muaragembong - Ramatillah, Diana Laila; Hakim, Muhammad Lukman; Hanif, Nita Aribah (UNIVERSITAS 17 AGUSTUS 1945 JAKARTA, 2024)
This community service program aims to enhance the understanding and skills of the coastal community in Muaragembong in utilizing the potential of the pidada mangrove (Sonneratia sp.) for health products. Despite its significant health benefits, including antioxidant, antibacterial, and anti-inflammatory properties, the utilization of pidada mangrove by the local community remains limited. This program was conducted through socialization, training, and hands-on workshops, educating participants on how to process pidada mangrove into health products such as herbal drinks, supplements, and skincare items. Before the training, only 28% of participants were aware of the health benefits of pidada mangrove, but after the training, 87% demonstrated a strong understanding of the topic. Post-training assessments showed a significant increase in knowledge, with the average quiz score rising from 45% to 89%. The majority of participants acknowledged that they had gained a better understanding of the potential of pidada mangrove and felt confident in developing small-scale products based on this resource. This program not only improves the community's health but also provides economic opportunities through the sustainable use of natural resources, thereby supporting mangrove ecosystem conservation.